Fascin Expression in Diffuse Large B-Cell Lymphoma, Anaplastic Large Cell Lymphoma, and Classical Hodgkin Lymphoma - Bakshi, Nasir A.; Finn, William G.; Schnitzer, Bertram; Valdez, Riccardo; Ross, Charles W. (Archives of pathology & laboratory medicine (1976), 2007)
Context.—Fascin is an actin-bundling protein involved in the formation of dendritic processes. Fascin is a sensitive marker for classical Reed-Sternberg cells and has a high negative predictive value for diagnosis of classical Hodgkin lymphoma (CHL). Fascin has been used to distinguish CHL from non-Hodgkin lymphoma. Recently, it was shown that fascin might not help differentiate CHL from anaplastic large cell lymphoma (ALCL). Moreover, fascin has not been extensively studied in the context of other large cell lymphomas. Objective.—To analyze fascin expression in diffuse large B-cell lymphoma (DLBCL) and also reexamine its usefulness in discriminating CHL from ALCL. Design.—Formalin-fixed, paraffin-embedded tissue samples from 41 cases of DLBCL, 30 cases of CHL, and 30 cases of ALCL were analyzed. Fascin expression was compared across each type of lymphoma with additional correlation between fascin positivity and ALK-1 expression in ALCL performed. Results.—Only 6 (14.6%) of 41 cases of DLBCL stained positively for fascin, with most neoplastic large cells exhibiting a weak staining pattern. Fifteen (50%) of 30 cases of ALCL showed positivity for fascin, with most large cells staining strongly. All 30 cases of CHL demonstrated intense positive staining. Sixty percent of fascin-positive ALCLs were positive for ALK-1, while 66.7% of fascin-negative ALCLs were positive for ALK-1. Conclusions.—Fascin is highly sensitive for CHL and has a very high negative predictive value (100% in this series) for distinguishing CHL from DLBCL or ALCL. However, the specificity and positive predictive value for fascin are much higher in distinguishing CHL from DLBCL than in distinguishing CHL from ALCL. Expression of fascin appears more useful in the differential diagnosis of CHL versus DLBCL than in the differential diagnosis of CHL versus ALCL.